2010
DOI: 10.1002/pros.21209
|View full text |Cite
|
Sign up to set email alerts
|

p53 Pro72Arg polymorphism and prostate cancer in men of African descent

Abstract: BACKGROUND p53 is a transcription factor that regulates the cell cycle, DNA repair, and apoptosis. A variant at codon 72, rs1042522, results in altered activities for p53 and is, notably, differentially distributed among different ethnic populations. However, associations of this variant with cancer in men of African descent have not been explored. Herein, we tested the hypothesis that rs1042522 was associated with prostate cancer (PCa) risk. MATERIALS AND METHODS Genotypes were determined by PCR-RFLP method… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
25
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(26 citation statements)
references
References 55 publications
1
25
0
Order By: Relevance
“…Studies carried out in Japan (22), China (23) and Northern India (24) reported the same increased association of the Pro allele with prostate cancer risk as the study by Quiñones et al (21), however, the studies of men in Argentina (27) and Iran (28) did not. One study by Ricks-Santi et al (26) found a significant association of the Arg allele with the prevalence of prostate cancer in populations of men of African descent.…”
Section: P21 C98a P21 C70t ------------------------------------------mentioning
confidence: 99%
See 1 more Smart Citation
“…Studies carried out in Japan (22), China (23) and Northern India (24) reported the same increased association of the Pro allele with prostate cancer risk as the study by Quiñones et al (21), however, the studies of men in Argentina (27) and Iran (28) did not. One study by Ricks-Santi et al (26) found a significant association of the Arg allele with the prevalence of prostate cancer in populations of men of African descent.…”
Section: P21 C98a P21 C70t ------------------------------------------mentioning
confidence: 99%
“…The two variants were considered wild-type, resulting in a non-conservative change (6,15). In certain studies the Pro allele was associated with increased prostate cancer risk (21)(22)(23)(24)(25), while in others the Arg allele was associated with prostate cancer predisposition (26). Other studies, mainly larger studies and meta-analyses, did not detect any association of the p53 codon 72 polymorphism with prostate cancer risk (27)(28)(29)(30).…”
Section: Introductionmentioning
confidence: 99%
“…According to the inclusion criteria, seven studies (Henner et al, 2001;Suzuki et al, 2003;Huang et al, 2004;Wu et al, 2004;Leiros et al, 2005;Quinones et al, 2006;Ricks-Santi et al, 2010) were included in this meta-analysis and 68 studies were excluded. The flow chart of the study selection is summarized in Figure 1.…”
Section: Studies Included In the Meta-analysismentioning
confidence: 99%
“…The Arg allele was differentiated from the Pro allele at codon 72 of TP53 by restriction fragment length polymorphism of PCR-generated amplicons using primers and the restriction enzyme BstU1 as published elsewhere. 10 Data were analyzed with Statview 5.0 (SAS Institute Inc., Cary, NC). Allele frequencies and genotypes were compared by the χ 2 test, and continuous variables by the Mann Whitney U test or Student's t test as applicable.…”
mentioning
confidence: 99%